Hubungan PHBS Rumah Tangga dengan Penggunaan Jamban di PPA ID-127 Kelurahan Ranomuut Kota Manado - Palandeng, Henry Malcom Frank; Rombot, Dina V.; Simanjuntak, Martin; Goni, Angel C. (UNIVERSITAS SAM RATULANGI, 2013)
Clean and Healthy Behavior is a picture of the family life’s pattern that’s always caring and keeping the healthiness of the whole family members. Clean and Healthy Behavior should be applied as early as possible to make a positive behavior of the health’s upkeep. The application of CHB in North Sulawesi in 2004 was only around 17,95% and for Minahasa was 16,67%. Those numbers are still far behind the 65% that was targeted in 2010. One of CHB’s Indicators is the availability of latrine. Latrine is made for people feces’ disposal. The latrine usage is purposed to keep the clean and health environment. This research is aimed to discover the relation between the CHB of household and the latrine usage in Children Development Center ID-127 Ranomuut District, Manado City. This research is an analytic research and using cross sectional method. The location is taken in CDC ID-127 Ranomuut District, Manado City with 68 respondents consist of parents of children in age’s 3-5 in CDC. The research that is examined by using chi square test in SPSS program, shows no significant correlation between CHB and latrine usage (p=0,000) and a strong prove to receive the null hypothesis which is no correlation between CHB and latrine usage in CDC ID-127 Ranomuut District, Manado City. Keywords: Clean and Healthy Behaviour of Household, Children Develompment Center ID-127